Perilaku Ibu Hamil dalam Memilih Tempat Bersalin di Wilayah Kerja Puskesmas Sorawolio Kecamatan Sorawolio Kota Baubau - La Ode Muh Taufiq, Nuriva, Rininta Andriani (Fakultas Kesehatan Masyarakat Universitas Dayanu Ikhsanuddin, 2021)
The place of birth is one of the factors that can affect the psychological condition of the mather. The choice of the right place of birth and birth attendants wil have a direct impact on maternal health. The are at least two choices for a place to give birth namely at the mother’s house or in the health care unit. The study aims to determine the behavior of pregnant women in choosing a place of birth in the work area of the Sorawolio health center, Sorawolio sub-district, Baubau city. The type research used is quantitative with a descriptive approach. With a population of 218 pregnant women who were drawn the sample size using the Michael fan Isaac formula to 68 respondents. The sample in this study using the Accidental Sampling method. Collecting data through primary data using questionnaire and making direct observations and secondary data. Collecting data through primary data using SPSS version 21 with univariate data analysis. The results of the statistical test found that the behavior of pregnant women choosing a place of birth in the working area of the city of Baubau Sorawolio, most of which had sufficient knowledge, as many 79,4%, positive attitude as much as 67,6%, but respondents had less action as many 52,9%. The conclusion of this research is the behavior of pregnant women in choosing a place of birth seen from the aspect of knowledge that is enough, and the attitude aspect is positive, but the aspect of action is still lacking. It is recommended for pregnant women to check their pregnancy routinely in terms of health and to choose delivery at a health facility